Managing stress among library staff in public university libraries in Ghana - Kodua-Ntim, K.; Akussah, H.; Adjei, E. (The Journal of Academic Librarianship, 2021)
The study investigated the management of stress by public university library staff in Ghana. The major purpose was to identify strategies that are employed by public university library staff to manage the stress they experience. One hundred and forty-four (144) respondents were sampled for the quantitative phase using the Fisher et al. (1998) formula for determining sample size, but for the qualitative phase nine (9) management staff were chosen. Purposive, simple random and convenience sampling techniques were employed. Questionnaires and interview guides were used as research instruments to gather relevant data for the study. Descriptive statistics, inferential statistics and thematic analysis were used as statistical tools to analyse the data. The study showed that indeed the library staff in public university libraries has a lot of stressful job events. However, it was indicated that library staff also adopt numerous coping strategies such as taking time off work and leave, positive thinking, building a strong human relationship and going for counselling in an attempt to manage their stress.
Research Article
Keywords: Causes; Library staff; Management; Strategies; Stress; Universities